Influence of post hatch dietary supplementation of fat on performance, carcass cuts and biochemical profile in Ven Cobb broiler - Rai, Komal Prasad (Vet World, 2015)
AIM: The present experiment was conducted to study the effect of post hatch dietary fat supplementation on performance of broiler chicken. MATERIALS AND METHODS: A total of 120 day-old Ven Cobb broiler chicks were randomly assigned to 4 treatment groups of 30 chicks in each (three replicates of 10 birds/treatment). The trial lasted for 35 days. The experimental design was a completely randomized design. Four types of diet were formulated for 1(st) week: T(1), T(2), T(3) and T(4) contained control diet with no added fat, 2.5, 5 and 7.5% fat, respectively. After 1(st) week post-hatch period chicks were fed ad libitum with the normal basal diet as per Bureau of Indian Standard recommendations till completion of the experiment (8-35 days). RESULTS: Significantly higher (p<0.05) body weight and improved feed conversion ratio (FCR) was recorded in birds fed 5% dietary fat at the end of the experiment whereas, feed intake was not significantly affected. Significantly (p<0.05) higher dressed weight was observed due to 5% fat supplementation than other groups whereas, it was not significant for other carcass cuts. No significant differences were observed in moisture, protein and lipid content of breast and thigh muscle of broiler due to supplemented fat whereas, 2.5% dietary fat significantly (p<0.05) increase the serum HI titer on day 28(th). In biochemical profile, higher serum albumin (g/dl) was recorded due to 5% fat supplementation whereas other biochemical components did not show any significance difference among treatments. CONCLUSION: It may be concluded that supplementation of fat in broilers diet improves the overall FCR, dressing percentage and gain more body weight.